The reflective cracking in the pavement overlay design - Pais, Jorge C. (2003)
This paper describes a new pavement overlay design method that takes into account the reflective cracking as the most predominant type of overlay distress. This phenomenon is characterized as the propagation of old cracks to the new pavement layer. The models proposed are based on a finite element model that closely approximates actual field phenomena based on measurements done on Arizona and Portugal. Test sections have been constructed to access the effect of overlay thickness, crack width and load to validate the design method. Crack activity under the effect of traffic loads was initially calculated and compared with field results, and strains in the zone above cracks were calculated. Expected performance of asphalt-rubber hot mix and conventional asphalt overlay was calculated using the proposed model and a conventional overlay design simulation was made.